2020
DOI: 10.1038/s41523-020-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic, immunophenotypic, and proteomics characteristics of low-grade phyllodes tumor and fibroadenoma: more similarities than differences

Abstract: Distinguishing low-grade phyllodes tumor from fibroadenoma is practically challenging due to their overlapping histologic features. However, the final interpretation is essential to surgeons, who base their management on the final pathology report. Patients who receive a diagnosis of fibroadenoma might not undergo any additional intervention while lumpectomy with wide margins is the standard of care for phyllodes tumor, which can have significant cosmetic consequences. We studied the clinical, immunophenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
2
12
0
1
Order By: Relevance
“…Although broadenomas and benign phyllodes tumors are recognized as distinct entities, their common overlapping histologic features (particularly between cellular FA and benign PT) makes the distinction challenging in daily practice. There are several comprehensive genetic and proteomic studies of FELs suggests that FAs and benign PTs share similar gene and protein expression pro le (9,10,18,23). Our study revealed that broadenomas (FAs), cellular broadenomas, and benign phyllodes tumors (PTs) manifest similar gene expression pro les.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although broadenomas and benign phyllodes tumors are recognized as distinct entities, their common overlapping histologic features (particularly between cellular FA and benign PT) makes the distinction challenging in daily practice. There are several comprehensive genetic and proteomic studies of FELs suggests that FAs and benign PTs share similar gene and protein expression pro le (9,10,18,23). Our study revealed that broadenomas (FAs), cellular broadenomas, and benign phyllodes tumors (PTs) manifest similar gene expression pro les.…”
Section: Discussionmentioning
confidence: 66%
“…In recent years, a wide range of studies have been performed on PTs and FAs with respect to their biomarker expression, genetic alterations, and molecular mechanisms, as potential tools to more reproducibly classify PTs and FAs (9)(10)(11). Gene expression pro ling is an additional approach which might help predict the biological behavior of FELs and provide insights for their clinical management, though studies using this technique remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that fibroadenomas, benign and some borderline phyllodes tumors share similar clinical features, immunohistochemical patterns, genetic aberrations, and outcomes. 2,3 For those lesions in which a definitive distinction between fibroadenoma and phyllodes tumor is difficult or not possible, some researchers suggested avoiding the diagnosis of phyllodes tumor and choosing a more conservative surgical approach. 2 It is generally acknowledged that the recurrence rate of phyllodes tumors is higher than that of fibroadenomas.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For those lesions in which a definitive distinction between fibroadenoma and phyllodes tumor is difficult or not possible, some researchers suggested avoiding the diagnosis of phyllodes tumor and choosing a more conservative surgical approach. 2 It is generally acknowledged that the recurrence rate of phyllodes tumors is higher than that of fibroadenomas. 4 Most fibroadenomas do not recur after complete excision, although there is a tendency to develop same-site recurrence after excision in adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Phyllodes tumours are uncommon fibroepithelial breast tumours that are capable of a wide range of biological behaviours, from benign to malignant [1]. They can appear at any age, with a median age of presentation of 42 to 45 years, and are often misdiagnosed as fibroadenomas [2,3]. Phyllodes tumours account for less than 1% of all breast tumours, and they rarely undergo a malignant epithelial transformation.…”
Section: Introductionmentioning
confidence: 99%